2015
DOI: 10.1136/bmjqs-2014-003803
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-understanding: an analysis of the dilution of value in healthcare

Abstract: None of the four aspects were understood at a level required to develop the management concept of VBHC. VBHC may be undergoing a process of dilution rather than diffusion. To break the cycle of management trends, we encourage a deeper reflective process about the translation of management concepts in healthcare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 41 publications
1
51
0
Order By: Relevance
“…[21] This study does not seek to answer whether this was done or not in this case, but other studies have shown that VBHC as a management strategy has been understood in different ways. [31,47] Understanding the concept is fundamental. Therefore it is important for a hospital management team that decides to implement a management innovation as VBHC in its organization to set explicitly defined goals and to state clearly what work is expected of the team members.…”
Section: Discussionmentioning
confidence: 99%
“…[21] This study does not seek to answer whether this was done or not in this case, but other studies have shown that VBHC as a management strategy has been understood in different ways. [31,47] Understanding the concept is fundamental. Therefore it is important for a hospital management team that decides to implement a management innovation as VBHC in its organization to set explicitly defined goals and to state clearly what work is expected of the team members.…”
Section: Discussionmentioning
confidence: 99%
“…Also, VBHC is gaining substantial interest in relation to several patient groups (including cancer [58], spinal disorders [59], and people living with complex long-term conditions [60]) and in many parts of the world (such as the US [61], Europe [5, 62], and Asia [63]). However, the label VBHC is sometimes used without deeper understanding of the original concept [64], though some promising results have also been presented. For example, the focus in VBHC on patient-reported health outcomes has led to reduced nausea after surgery, and the focus on integration of care within and across facilities has led to an increase of available beds for patients in need of admission [65].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…DO SOMETHING ABOUT IT. NOW.” Such pseudo‐understanding of complexity science did not help the Region amplify any desirable patterns; what was amplified was the cacophony of incongruent initiatives. (A complexity‐informed analysis of the Region's vacillation between centralization and decentralization will be presented separately.…”
Section: Discussionmentioning
confidence: 99%